Identitas Kultural dan Nasionalisme Jarak Jauh Kaum Diaspora dalam Novel Rojak dan Bricklane - Nugraheni, Heri Dwi Santoso dan Yunita (Sasando, 2020)
People leaving their countries to become permanent residents of other countries and/or change their nationaliites are often seen unpatriotic and having not nationalistic spirits. However, facts show that many of them still show nationalism towards their homelands. This kind of nationalism is called long distance nationalism. Considering literature as a mirror of society, such an issue is found in several literary works. This study was conducted on Rojak (an Indonesian novel) and Bricklane (and English novel), in which diaspora characters were found. The research aimed at finding out if long-distance nationalistic spirits could be found, and how these characters shared their views on their homelands. Method used was comparative literary studies with eclectic approach (combination of structural and postcolonial approaches). Results showed that such diaspora figures, with different personalities and migration motives, represent different cultural identities. Besides, the differences of the migration motives also made impacts on their long distance nationalisms. It is concluded that we cannot generalize diaspora peoples qualities of long distance nationalism for they deal with various aspects, including ambivalences to certain extents.